Pengembangan Modul Pembelajaran Berbasis QR Code sebagai Penunjang Keterampilan Gerak Dasar Permainan Bolavoli bagi Siswa Kelas VIII SMP Negeri 1 Jombang - Ossa Viantina; Basuki Basuki; Risfandi Setyawan; Guntum Budi Prasetyo (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Based on the results of the needs analysis conducted at SMPN 1 Jombang, multimedia technology-based learning media is needed in learning volleyball basic movement skills to improve learning outcomes and student interest in learning. So this study aims to develop learning media in the form of learning modules using QR Code. The research method used is R&D